TRENDS IN TOURISM RESEARCH IN MALAYSIA: A BIBLIOMETRIC ANALYSIS - Muhammad Hanif Othman; Zouhair Mohd Rosli, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This article presents a bibliometric review analyzing 43 years of research published between 1979 and 2022 from the Elsevier Scopus database. Through bibliographical analysis of 1,956 Scopus-indexed documents, the review found that this is very recent literature with over 89% of the relevant documents published since 2010. The contributions of institutional tourism publications by affiliation showed that Universiti Teknologi Malaysia (UiTM) had the highest number of publications. Meanwhile the Tourism Management, Current Issues in Hospitality and Tourism Research and Innovations and Planning Malaysia published the most significant number of publications related to tourism research. To the best of the researchers’ knowledge, this is the first bibliometric study to analyze tourism research in Malaysia.